Incentives, Self-Selection, and Coordination of Motivated Agents for the Production of Social Goods - Kevin Bauer; Michael Kosfeld; Ferdinand von Siemens (Institute of Labor Economics (IZA), 2021)
We study, theoretically and empirically, the effects of incentives on the self-selection and coordination of motivated agents to produce a social good. Agents join teams where they allocate effort to either generate individual monetary rewards (selfish effort) or contribute to the production of a social good with positive effort complementarities (social effort). Agents differ in their motivation to exert social effort. Our model predicts that lowering incentives for selfish effort in one team increases social good production by selectively attracting and coordinating motivated agents. We test this prediction in a lab experiment allowing us to cleanly separate the selection effect from other effects of low incentives. Results show that social good production more than doubles in the low-incentive team, but only if self-selection is possible. Our analysis highlights the important role of incentives in the matching of motivated agents engaged in social good production.
Keywords: C91; D90; J24; J31; M52; 330; incentives; intrinsic motivation; self-selection; public service